2007
DOI: 10.1121/1.2799901
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating noise in social context: The effect of procedural unfairness on noise annoyance judgments

Abstract: General dosage-response curves typically over- or underestimate the actual prevalence of noise annoyance for specific groups of individuals. The present study applies a social psychological approach to noise annoyance that helps to understand and predict collective deflections from the curve. The approach holds that being exposed to man-made sound is more than mere exposure; it is a social experience, too: You expose Me. In effect, social aspects of the situation, like the evaluation of the sound management pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…For example, Glaser and Singer [8] have shown via several experiments that an individual's level of perceived control over the degree of noise exposure influences a person's noise reaction. In similar fashion, Maris et al [9,10] have shown that the fairness of the procedures preceding the actual exposure to noise influences the degree of reported noise annoyance. Although these studies can firmly establish causality for the sample under investigation, the results cannot easily be generalized towards a population living around an airport.…”
Section: Introductionmentioning
confidence: 83%
“…For example, Glaser and Singer [8] have shown via several experiments that an individual's level of perceived control over the degree of noise exposure influences a person's noise reaction. In similar fashion, Maris et al [9,10] have shown that the fairness of the procedures preceding the actual exposure to noise influences the degree of reported noise annoyance. Although these studies can firmly establish causality for the sample under investigation, the results cannot easily be generalized towards a population living around an airport.…”
Section: Introductionmentioning
confidence: 83%
“…In laboratory studies, it has already been shown that noise annoyance can be diminished through fair procedures [13] and increases by unfair procedures. [14] Furthermore, trust in authorities is related to the expectation how noise will develop in the future, and the belief that noise could be prevented. [6,11] Positive social evaluations of the noise source, for example, the belief of its importance, are deemed to attenuate annoyance.…”
Section: Introductionmentioning
confidence: 99%
“…There are two potential channels through which one might imagine this deliberate removal of individual agency might negatively affect future co-operation. One channel relates to the psychological and emotional response to being deliberately excluded from a choice process, triggering a response to perceived procedural unfairness 2 [3][4][5][6][7]. The second channel relates to the response to the material inequality that is produced through the process of deliberate exclusion, triggering inequality aversion [8][9][10].…”
Section: Does Exclusion Reduce Pro-sociality?mentioning
confidence: 99%
“…However, there is mixed evidence on this effect with some finding no effects [43,45], others showing positive effects [38,42], as still others finding lower levels of cooperation [40,44,49] 6 .…”
Section: Does Inequality Affect Public Goods Provision?mentioning
confidence: 99%
See 1 more Smart Citation